Pseudomonas fluorescens and Trichoderma asperellum Enhance Expression of Gα Subunits of the Pea Heterotrimeric G-protein during Erysiphe pisi Infection - Patel, Jai S.; Sarma, Birinchi K.; Singh, Harikesh B.; Upadhyay, Ram S.; Kharwar, Ravindra N.; Ahmed, Mushtaq (Frontiers in Plant Science, 2016)
We investigated the transcript accumulation patterns of all three subunits of heterotrimeric G-proteins (Gα1&2, Gβ and Gγ) in pea under stimulation of two soil-inhabiting rhizosphere microbes Pseudomonas fluorescens OKC and Trichoderma asperellum T42. The microbes were either applied individually or co-inoculated and the transcript accumulation patterns were also investigated after challenging the same plants with a fungal biotrophic pathogen Erysiphe pisi. We observed that mostly the transcripts of Gα 1 and 2 subunits were accumulated when the plants were treated with the microbes (OKC and T42) either individually or co-inoculated. However, transcript accumulations of Gα subunits were highest in the T42 treatment particularly under the challenge of the biotroph. Transcript accumulations of the other two subunits Gβ and Gγ were either basal or even lower than the basal level. There was an indication for involvement of JA-mediated pathway in the same situations as activation of LOX1 and COI1 were relatively enhanced in the microbe co-inoculated treatments. Non-increment of SA content as well as transcripts of SA-dependent PR1 suggested non-activation of the SA-mediated signal transduction in the interaction of pea with E. pisi under the stimuli of OKC and T42. Gα1&2 transcript accumulations were further correlated with peroxidases activities, H2O2 generation and accumulation in ABA in pea leaves under OKC and T42 stimulations and all these activities were positively correlated with stomata closure at early stage of the biotroph challenge. The microbe-induced physiological responses in pea leaves finally led to reduced E. pisi development particularly in OKC and T42 co-inoculated plants. We conclude that OKC and T42 pretreatment stimulate transcript accumulations of the Gα1 and Gα2 subunits of the heterotrimeric G protein, peroxidases activities and phenol accumulation in pea during infection by E. pisi. The signal transduction was possibly mediated through JA in pea under the stimulus of the microbes and the cumulative effect of the co-inoculated microbes had a suppressive effect on E. pisi conidial development on pea leaves.